Transgenic expression of the HERV-W envelope protein leads to polarized glial cell populations and a neurodegenerative environment - Gruchot, Joel; Lewen, Isabel; Dietrich, Michael; Reiche, Laura; Sindi, Mustafa; Hecker, Christina; Herrero, Felisa; Charvet, Benjamin; Weber-Stadlbauer, Ulrike; Hartung, Hans-Peter; Albrecht, Philipp; Perron, Hervé; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2023)
The human endogenous retrovirus type W (HERV-W) has been identified and repeatedly confirmed as human-specific pathogenic entity affecting many cell types in multiple sclerosis (MS). Our recent contributions revealed the encoded envelope (ENV) protein to disturb myelin repair by interfering with oligodendroglial precursor differentiation and by polarizing microglial cells toward an axon-damage phenotype. Indirect proof of ENV's antiregenerative and degenerative activities has been gathered recently in clinical trials using a neutralizing anti-ENV therapeutic antibody. Yet direct proof of its mode of action can only be presented here based on transgenic ENV expression in mice. Upon demyelination, we observed myelin repair deficits, neurotoxic microglia and astroglia, and increased axon degeneration. Experimental autoimmune encephalomyelitis activity progressed faster in mutant mice equally accompanied by activated glial cells. This study therefore provides direct evidence on HERV-W ENV's contribution to the overall negative impact of this activated viral entity in MS.
Keywords: endogenní retroviry; neuroglie; Humans; Endogenous Retroviruses; endogenous retrovirus; Multiple Sclerosis; Myelin Sheath; geneticky modifikovaná zvířata; Neuroglia; lidé; zvířata; myši; Mice; glia; Animals, Genetically Modified; myelin repair; multiple sclerosis; roztroušená skleróza; Animals; neurodegeneration; myelinová pochva